STRATEGI PONDOK PESANTREN RAUDHATUL ULUM 1 MERANTI DALAM MENGEMBANGKAN KEMANDIRIAN SANTRI TAHUN ANGKATAN 2020 - 2021: strategi kemandirian santri - ZAINI SUHRA WARDI (J-MD Jurnal Manajemen Dakwah, 2022)
The purpose of this study was to determine the Strategy of the Raudhatul Ulum 1 Meranti Islamic Boarding School in Developing Student Independence. This research focuses on 1. The steps for determining the development strategy: 2. The application of the development strategy: 3. Evaluation of the boarding school administrators in developing the independence of students. In general, the results of this study can be concluded that the independence development strategy carried out by the Raudhatul Ulum 1 Meranti Islamic Boarding School, the first steps of the development strategy, is to analyze the hobbies of students, giving freedom to students in developing their skills. The second implementation of the development strategy consists of determining rules, supervising, providing motivation, providing facilities, punishment for students who violate. The three evaluations of the boarding school administrators are carried out after completing daily activities, once every six months and making reports.